Biomass and carbon sequestration potential in different agroforestry systems in Giri catchment of North Western Indian Himalaya - Singh, Matber; Gupta, B.; Sarvade, S.; Awasthe, R.K. (Indian Journal of Agroforestry, 2020)
Agroforestry has been recognized as having the greater potential for biomass and C sequestration of all the land uses; however, understanding of C sequestration in very specific agroforestry systems is at rudimentary. In this study, different agroforestry systems existing on arable and non-arable lands in Giri catchment of North Western Himalayan region of India were evaluated for biomass and C sequestration.The vegetation study on six vegetation systems viz., agri-silviculture (AS), agri-horticulture (AH), agri-horti-silviculture (AHS), agri-silvi-horticulture (ASH), silvi-pasture (SP) and grassland (GS) were carried out during 2011-12 for their biomass and carbon sequestration potential analysis. The highest aboveground, belowground and total biomass i.e., 70.63, 18.61 and 89.24 t ha-1, respectively, was recorded in SP in which trees contributed 95.92 % C in aboveground biomass. Among the agroforestry systems aboveground, belowground and total biomass of vegetation decreased in the order: ASH > AHS > AS > AH. Whereas, maximum soil organic carbon was observed in GS, which was statistically at par with AH and AHS systems. The carbon stored in vegetation + soil of SP (94.38 t C ha-1) was significantly higher than other systems and it was 1.69 times higher than GS (55.91 t C ha-1).